Experimental Investigation On The Use Of Natural Waste Fibres As Acoustic Material Of Noise Silencer - Ahmad Yusuf, Ismail; M. J., Chen; M. F., Azizi; M. A., Sis (Penerbit Akademia Baru, 2016)
The use of synthetic materials as an acoustic material of absorptive silencer is still dominant in the industry. These materials not only have an impact on human health, but also contribute to environmental pollution. This study presents an experimental investigation on the use of natural fibres i.e. coconut and paddy straw fibres as a substitution for the synthetic materials. The samples were fabricated with several different densities of the fibres to identify the most effective composition to absorb sound. The experiments were conducted using the dynamic insertion loss technique as the most applied and simplest method to observe silencer performance. It is found that the natural fibres perform well as absorptive materials and prospective to be used in the future.